Makna dan Tradisi Seserahan Kue Jaddah dalam Perspektif Masyarakat Jawa - Amri, Amri; Masitho, Nadia (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
The tradition of seserahan is an integral part of wedding ceremonies in various regions of Indonesia, including among the Javanese community, which is rich in cultural rituals. One unique aspect of this tradition is the presentation of Kue Jaddah by the groom to the bride during the seserahan procession. This study aims to explore the significance of the Kue Jaddah tradition in Javanese wedding seserahan and analyze it from an Islamic perspective. The research employs a qualitative descriptive method, collecting data through observations and in-depth interviews with purposively selected informants. The findings reveal that Kue Jaddah, made from glutinous rice and requiring a lengthy preparation process, symbolizes patience and harmony in marriage. Its sticky texture is believed by the Javanese community to represent the strong bond between husband and wife. From an Islamic perspective, this tradition falls into the category of (‘Urf Shahih) as it does not involve elements of polytheism, and Kue Jaddah is not a prohibited food. The tradition reflects cultural values that strengthen family ties and remains relevant within an Islamic context. This study is expected to provide insights into how local traditions can be preserved and harmonized with religious values to enrich social life.